The needs of accessibility audit in facilities management for improving inclusive access/ Zuraihana Ahmad Zawawi ... [et al.] - Ahmad Zawawi, Zuraihana; Kamarudin, Hikmah; Mohammad Ali, Irwan; Narotama, Mohamad Rachmadian (Universiti Teknologi MARA, Perak, 2024)
Accessibility is not just a technical issue, but it is also a term in which the environment tells whether someone is being included or excluded. An access audit in facilities management is a critical process aimed at evaluating and improving the accessibility of a facility to ensure it is inclusive for all users, including those with disabilities. Thus, this paper examines the needs of accessibility audit in facilities management in an effort to enhance inclusive access within the built environment. Through the extensive review of existing research, this paper identifies the needs and benefits of having accessibility audits in facilities management to promote accessibility for individuals with diverse needs. The findings highlight several key needs of accessibility audit in facilities management to enhance inclusive access in the built environment, including standards compliance, enhancing inclusivity, improving safety and risk management, cost efficiency, and operational efficiency. This paper emphasizes important implications for proactive facilities management approaches in creating an inclusive built